2021
DOI: 10.18662/rrem/13.2/421
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Foreign Languages Blended Learning in COVID-19 Conditions by Means of Mobile Applications

Abstract: The article discusses the theoretical aspects of the organization of blended foreign language learning caused COVID-19 under the conditions of the quarantine. We analyzed different points of view on the process of using mobile applications in the study of foreign languages. We considered the possibilities of four mobile applications Duolingo, Simpler, Hello Talk, EWA with their main advantages and disadvantages. In the context of the research topic, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…There are several pedagogical advantages of using mobile technology in BL delivery modality; for instance, Bardus and his colleagues [77] did research involving 100 students at the universities of Karazin and Berdyansk. Their findings indicated that the use of mobile applications to learn foreign languages in BL had a favorable effect on students' motivation and perspective of language learning.…”
Section: Mobile Applications-assisted Instruction and Physical Educat...mentioning
confidence: 99%
“…There are several pedagogical advantages of using mobile technology in BL delivery modality; for instance, Bardus and his colleagues [77] did research involving 100 students at the universities of Karazin and Berdyansk. Their findings indicated that the use of mobile applications to learn foreign languages in BL had a favorable effect on students' motivation and perspective of language learning.…”
Section: Mobile Applications-assisted Instruction and Physical Educat...mentioning
confidence: 99%
“…A single pedagogical approach is insufficient to improve Thai high school students' language and cognitive skills, and the use of an additional novel pedagogical strategy, such as mobile-assisted language learning (MALL), is needed. Researchers have examined the effectiveness of MALL on English language learning and critical thinking skills and concluded that mobile devices can improve students' learning, while students also tend to have universally positive attitudes toward the use of this technology to promote linguistic and critical thinking development (Each & Suppasetseree, 2021;Gaber, 2015;Bardus, 2021). However, even a combination of MALL and BL may not be adequate to sharpen Thai high school students' critical reading skills.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the scientific literature has shown that the problem of the quality of education has become highly relevant since the onset of the pandemic (Chick et al, 2020;Elumalai et al, 2021). Scientists consider various aspects of learning during a pandemic and online learning in general: satisfaction with the online learning process (Chen et al, 2020); adaptation and communication in the digital space (Dorsi et al, 2021;Plass & Pawar, 2020a;2020b;Vanherle, 2021); motivation in online learning environments (Dragon, 2019); new forms of forced online interaction (Bardus, et al, 2021;Nalyvaiko, et al 2021;Plass & Pawar, 2020a;Serhan, 2020); comparison of online and offline learning (Goss et al, 2021); monitoring in higher education (Lane & D'Mello, 2018); risks and prospects of forced distance learning (Neuwirth et al, 2021;Zhu & Liu, 2020); involvement in the learning process (Wang, 2020).…”
Section: Introductionmentioning
confidence: 99%